2014
DOI: 10.4161/psb.29230
|View full text |Cite
|
Sign up to set email alerts
|

The roles of anion channels inArabidopsisimmunity

Abstract: Plants respond to constant challenges from microbial pathogens by employing a 2-layered innate immune system. 1 The first layer, namely pathogen-associated pattern (PAMP)-triggered immunity (PTI), is triggered by molecular patterns conserved on many types of microbes. However, adapted pathogens can secret effector proteins into host cells to suppress PTI. In turn, plants have evolved additional receptors that detect such effectors and mount a second-layer of defense, called effector-triggered immunity (ETI). 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Clalso enhanced plant resistance to pathogen infection by suppressing bacterial multiplication in intercellular spaces, and this enhancement is partially dependent on the SA pathway but not PTI responses, especially those mediated by FLS2 (Figure 2). This result indicated that the mechanism by which Cltreatment enhanced disease resistance differed from that resulting from anion channel mutants or stimulated by channel inhibitors (Guo et al, 2014a(Guo et al, , 2014b. Moreover, in the absence the pathogen infection, the genes related to immune responses and defense metabolites were downregulated (Supplementary Figure S4D), which is consistent with the observation that salt treatment suppresses the SA pathway.…”
Section: Clsalt Suppresses Cell Death In Acd5supporting
confidence: 80%
“…Clalso enhanced plant resistance to pathogen infection by suppressing bacterial multiplication in intercellular spaces, and this enhancement is partially dependent on the SA pathway but not PTI responses, especially those mediated by FLS2 (Figure 2). This result indicated that the mechanism by which Cltreatment enhanced disease resistance differed from that resulting from anion channel mutants or stimulated by channel inhibitors (Guo et al, 2014a(Guo et al, , 2014b. Moreover, in the absence the pathogen infection, the genes related to immune responses and defense metabolites were downregulated (Supplementary Figure S4D), which is consistent with the observation that salt treatment suppresses the SA pathway.…”
Section: Clsalt Suppresses Cell Death In Acd5supporting
confidence: 80%
“…Недавно продемонстрирована ключевая роль быстрых (R-тип) и медленных (S-тип) анионных каналов в анионной утечке из листьев A. thaliana (L.) Heynh. при добавлении в среду бактериального элиситора flg22 [61]. Это указывает на то, что утечка электролитов при патогенном стрессе связана не только с механическим повреждением тканей, а также на то, что она может вовлекать контролируемый механизм -активацию ионных каналов.…”
Section: утечка электролитов из клеток корня высших растений при возд...unclassified
“…For example, the chloride channel family protein CLCd can negatively regulate microbe pattern-triggered immunity (PTI), possibly via altered pH in the Golgi complex (Guo et al, 2014b). Pharmacological treatments showed that anion channels differentially participated in PTI and effector-triggered immunity (Guo et al, 2014a), but whether changing Cllevels by irrigation would affect plant biotic responses remains unclear. Yang et al (2019) found that pre-irrigation with 300 mM NaCl drastically inhibited the cell-death phenotype of acd5 mutants, which lack ceramide kinase and exhibit accelerated cell death (Liang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the chloride channel family protein CLCd can negatively regulate microbe pattern-triggered immunity (PTI), possibly via altered pH in the Golgi complex ( Guo et al., 2014b ). Pharmacological treatments showed that anion channels differentially participated in PTI and effector-triggered immunity ( Guo et al., 2014a ), but whether changing Cl - levels by irrigation would affect plant biotic responses remains unclear.…”
Section: Introductionmentioning
confidence: 99%